Green Chemistry Meets Advanced Materials: Synthesis and Adsorption Performance of Ti3CNTx MXenes for Basic Red 46 Dye Removal - Aydin, Ekrem; Celik, Aytekin; Kose, Yusuf; Hasar, Halil (Springer Int Publ Ag, 2025)
In this study, Ti3CNTx MXene nanosheets were synthesized from Ti3AlCNTx MAX phase via two selective Al-etching routes: (i) direct hydrofluoric acid (HF) treatment and (ii) in-situ HF generation using a LiF + HCl mixture. Both approaches were systematically compared to evaluate their effects on structural integrity, surface chemistry, and adsorption performance toward the cationic dye Basic Red 46 (BR 46). Comprehensive physicochemical characterizations-including SEM-EDX, XRD, XPS, Raman spectroscopy, AFM, contact angle analysis, and TGA-confirmed successful Al removal and MXene formation for both methods, with notable differences in surface terminations and layer morphology. Batch adsorption experiments were conducted across a wide range of pH values (2-11), temperatures (25-60 degrees C), contact times (0-90 min), adsorbent dosages (0.05-0.40 g), and initial dye concentrations (10-50 mg/L). The HF-etched Ti3CNTx exhibited rapid adsorption, achieving 99.6% removal at pH 2 within 20 min, whereas the LiF + HCl-etched sample demonstrated superior performance at moderate-to-alkaline pH and maintained high efficiency at lower dosages. Langmuir isotherm fitting revealed maximum adsorption capacities of 19.24 mg/g (HF route) and 28.01 mg/g (LiF + HCl route), supporting monolayer adsorption on homogeneous sites. Temperature-dependent studies further indicated an endothermic and spontaneous adsorption mechanism. Overall, the LiF + HCl route offers a greener and safer alternative to conventional HF etching while delivering competitive adsorption performance, improved structural stability, and faster equilibrium. These findings highlight the potential of sustainably synthesized Ti3CNTx MXenes as high-performance adsorbents for dye-laden industrial wastewater treatment.
Keywords: Ti(3)CNTx MXene; Adsorption; Hydrofluoric acid (HF) etching; Basic red 46 (BR 46)